Natural abundance δ13C constraints on the detection of microplastic-derived carbon in freshwater environments - Maier, Jan; Barth, Johannes; Ruess, Liliane; Castiglione, Kathrin; Blenk, Patrik; Visser, Anna-Neva (Environmental Pollution, 2026)
Microplastics (MPs) are increasingly recognized as emerging pollutants in freshwater systems. Detecting and tracing MP-derived carbon in aquatic food webs, however, remains unresolved, limiting our understanding of ecological impacts. Here, we evaluate the potential and limitations of natural abundance stable carbon isotope measurements (δ13C) as a tool to identify MP signals in freshwater ecosystems. For this purpose, two freshwater algae, Chlorella vulgaris and Chlamydomonas reinhardtii, were exposed under controlled laboratory conditions to one non-biodegradable polymer, low-density polyethylene (LDPE), and two biodegradable polymers, polylactic acid (PLA) and polybutylene adipate-co-terephthalate (PBAT), to assess isotope composition and growth. Laboratory data were complemented by particulate organic carbon (δ13CPOC) measurements from seasonal Danube River campaigns (2023–2024) with modeled predictions based on dissolved organic carbon (δ13CDIC). MP exposure did not inhibit algae growth, but C. vulgaris exhibited significant (p <0.05) δ13C enrichment (+4 to +5 ‰), whereas C. reinhardtii showed no isotopic response. These shifts were unrelated to polymer isotope values and likely reflect indirect physiological stress rather than assimilation of polymer-derived carbon. Complementary binary mixing experiments further confirmed that measurable isotopic shifts occur only at unrealistically low algae-to-MP ratios (≤10:1), underscoring the limited sensitivity of isotope mass balances. Field surveys revealed pronounced seasonal δ13CPOC variability in the Danube, spanning 7.4 ‰ annually. Yet deviations from modeled expectations were inconsistent with MP inputs and instead reflected natural drivers such as productivity and remineralization. Overall, while natural abundance δ13C can capture subtle algae responses to MP exposure under laboratory conditions, its diagnostic power for tracing MP-derived carbon in complex freshwater systems appears limited.
CRIS-Team Scopus Importer:2025-12-05
Keywords: (7): stable isotope analysis; Aquatic pollution; Chlamydomonas reinhardtii; Chlorella vulgaris; Danube river; Non-biodegradable and biodegradable polymers; Particulate organic carbon (POC)